2020
DOI: 10.1021/acsabm.9b00885
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Compatible Poly(2-methoxyethyl acrylate) Induces Blebbing-like Phenomenon and Promotes Viability of Tumor Cells in Serum-Free Medium

Abstract: Circulating tumor cells (CTCs) are highly related to tumor metastasis and an effective technique of detecting/isolating CTCs has been expected to be established for tumor treatments. Previously, we reported that platelets cannot adhere but tumor cells can adhere on poly(2-methoxyethyl acrylate) (PMEA) substrate. In this study, we report that cell viability of human fibrosarcoma (HT-1080) cells was promoted on PMEA substrate in serum-free medium. The significant blebbing-like phenomenon and spontaneous formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The base system showed a hump in the region of 25–35 2θ, BGT5 had its main hump in the range of 22–30 2θ, BGT7.5 exhibited a hump in the region of 10–25 2θ, and BGT10 showed a main hump in the range of 18–32 2θ. Same results have been reported for the inclusion of different transition metals in several studies; however, in most of these studies, no remarkable changes were observed in the amorphous nature of glass [ 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 77%
“…The base system showed a hump in the region of 25–35 2θ, BGT5 had its main hump in the range of 22–30 2θ, BGT7.5 exhibited a hump in the region of 10–25 2θ, and BGT10 showed a main hump in the range of 18–32 2θ. Same results have been reported for the inclusion of different transition metals in several studies; however, in most of these studies, no remarkable changes were observed in the amorphous nature of glass [ 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 77%
“…Although it was unclear whether the blebbing types were phagocytotic, apoptotic, or migratory, the blebbing-like phenomenon of HT-1080 cells occurred on PMEA substrates under serum-free conditions, leading to an increase in cell viability . The interaction of cells and substrates is related to the factor to induce blebbing formation of cells. , To verify the effect of adhesion strength on the blebbing formation, we first investigated the differences in blebbing formation and cell morphology of cells adhered on PET, PBA, and PMEA.…”
Section: Resultsmentioning
confidence: 99%
“…The amoeboid movement of round cells is driven by actomyosin-based cortical contraction with blebbing formation, which is modulated by the activation of ROCK signaling. , ROCK inhibitors convert the movement and shape of cells from amoeboid (round shape) to mesenchymal (spread shape). Our previous report and the present study revealed that HT-1080 cells moved slowly by amoeboid movement with blebbing formation on PMEA substrates . To ascertain the effect of the ROCK pathway on the movement of cells, HT-1080 cells adhered to substrates were treated with Y-27632, a ROCK inhibitor (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations